The Peritoneal Tuberculosis Mimicking Intraabdominal Pathology: Report of Three Cases - Aydoğmuş, Serpil; Keskin, Levent; Üstüner, Işık; Turgut, Olcay; Çelen, Emine; Avşar, Filiz (Gynecology Obstetrics & Reproductive Medicine, 2012)
Tuberculosis incidence increases worldwide and it is still a public health problem particularly in developing countries like Turkey. We aimed to present in this report 3 peritoneal/pelvic tuberculosis cases required diagnostic laparatomy due to malignity or abscess pre-diagnosis based on the presence clinical manifestations, such as pelvic pain, mass, ascites and increased CA-125 level, mimicking pelvic pathology. Peritoneal/pelvic tuberculosis should be absolutely considered in the differential diagnosis in cases with a presumptive diagnosis of pelvic malignancy or abscess with ascites, particularly in developing countries.